2019
DOI: 10.21865/ridep52.3.01
|View full text |Cite
|
Sign up to set email alerts
|

Validez de Constructo del Cuestionario Internacional de Actividad Física en Universitarios Españoles

Abstract: ResumenEste estudio tuvo como objetivo aportar información sobre la validez de constructo de la versión corta adaptada al español del cuestionario IPAQ empleando como variable de contraste la condición física. Estudio longitudinal-correlacional en el que 64 estudiantes universitarios (75% hombres) contestaron el IPAQ y realizaron tests de eficiencia cardiovascular, fuerza, agilidad y flexibilidad, durante tres años. Se encontraron correlaciones significativas y mantenidas en el tiempo entre la estimación de la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
0
6
0
4
Order By: Relevance
“…PA before quarantine was measured by a short version of the international PA questionnaire (IPAQ), Spanish version (Cancela et al, 2019). This measure assesses the types of intensities of PA and the amount of time that people spend sitting as part of their daily lives, considered in metabolic equivalent of task (MET)-min/week.…”
Section: Physical Activity Patterns and Anthropometric Characteristicsmentioning
confidence: 99%
“…PA before quarantine was measured by a short version of the international PA questionnaire (IPAQ), Spanish version (Cancela et al, 2019). This measure assesses the types of intensities of PA and the amount of time that people spend sitting as part of their daily lives, considered in metabolic equivalent of task (MET)-min/week.…”
Section: Physical Activity Patterns and Anthropometric Characteristicsmentioning
confidence: 99%
“…According to Eurofit normative values [ 21 ], the U14, cadets and junior karatekas assessed in this research showed a higher level of physical fitness than the general population of the same age. Similarly, the U21 karatekas showed higher fitness levels than those shown by populations of similar age [ 22 ]. This finding is expected since participants in this study were top karatekas who were taking part in high-level competitions.…”
Section: Discussionmentioning
confidence: 99%
“…La valoración del tiempo invertido en la práctica de AF para los grupos control y experimental TIC se llevó a cabo mediante el Cuestionario IPAQ S7 (Cancela et al, 2019), cuya fiabilidad es de r = .76; IC 95%: .73-.77 (Craig et al, 2003;Mantilla & Gómez-Conesa, 2007). La elección de esta herramienta obedeció a criterios de economía y facilidad a la hora de utilizarlo (Yu et al, 2015).…”
Section: Instrumentosunclassified